2016
DOI: 10.1016/j.redox.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Levels of inflammation and oxidative stress, and a role for taurine in dystropathology of the Golden Retriever Muscular Dystrophy dog model for Duchenne Muscular Dystrophy

Abstract: Duchenne Muscular Dystrophy (DMD) is a fatal skeletal muscle wasting disease presenting with excessive myofibre necrosis and increased inflammation and oxidative stress. In the mdx mouse model of DMD, homeostasis of the amino acid taurine is altered, and taurine administration drastically decreases muscle necrosis, dystropathology, inflammation and protein thiol oxidation. Since the severe pathology of the Golden Retriever Muscular Dystrophy (GRMD) dog model more closely resembles the human DMD condition, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 106 publications
3
49
1
1
Order By: Relevance
“…4). Consistent with this, levels of the classic markers for neutrophils, MPO and neutrophil elastase, closely correspond with elevated protein carbonylation, chlorotyrosine formation and thiol oxidation markers in dystrophic skeletal muscles of mdx mice and GRMD dogs (Terrill et al, 2016a). We have also shown that reversible protein thiol oxidation is especially localised in foci of myonecrosis (Iwasaki et al, 2013), and occurs on muscle proteins such as myosin heavy chain, myosin light chain and tropomyosin, as well as on the glycolytic proteins phosphoglycerate mutase and triosephosphate isomerase (Armstrong et al, 2011;El-Shafey et al, 2011;Iwasaki et al, 2013;Radley-Crabb et al, 2012;Terrill et al, 2012Terrill et al, , 2013aTerrill et al, ,b, 2016a.…”
Section: Reversible Oxidation Of Protein Thiolssupporting
confidence: 70%
See 1 more Smart Citation
“…4). Consistent with this, levels of the classic markers for neutrophils, MPO and neutrophil elastase, closely correspond with elevated protein carbonylation, chlorotyrosine formation and thiol oxidation markers in dystrophic skeletal muscles of mdx mice and GRMD dogs (Terrill et al, 2016a). We have also shown that reversible protein thiol oxidation is especially localised in foci of myonecrosis (Iwasaki et al, 2013), and occurs on muscle proteins such as myosin heavy chain, myosin light chain and tropomyosin, as well as on the glycolytic proteins phosphoglycerate mutase and triosephosphate isomerase (Armstrong et al, 2011;El-Shafey et al, 2011;Iwasaki et al, 2013;Radley-Crabb et al, 2012;Terrill et al, 2012Terrill et al, , 2013aTerrill et al, ,b, 2016a.…”
Section: Reversible Oxidation Of Protein Thiolssupporting
confidence: 70%
“…with mass spectrometry or by immunoblotting using an antibody that can detect halogenated tyrosine (Kato et al, 2005;Winterbourn, 2002). We have shown an increase in tyrosine halogenation in GRMD muscle (Terrill et al, 2016a).…”
Section: Irreversible Oxidative Damage Of Macromoleculesmentioning
confidence: 88%
“…In patients with DMD and mdx mice, muscle degeneration results from several pathogenic processes, and oxidative stress, fibrosis, and chronic inflammation have major effects on the functional impairment of muscle and on disease progression. 35,36 Our study reveals for the first time that the treatment of mdx mice with catalpol reduces fibrosis and inflammation, major pathogenic pathways that mediate muscle degeneration and functional impairment in DMD. These pathological changes translated into improved skeletal muscle function, as reflected in grip strength in vivo and specific force production and recovery in vitro.…”
Section: Discussionmentioning
confidence: 83%
“…Dystrophic patients and mdx mice showed high levels of reactive oxygen species (ROS) and lipid peroxidation [ 5 , 14 ]. Our research group and other researchers have already demonstrated the beneficial effect of antioxidant treatment, such as N-acetylcysteine, ascorbic acid, green tea and taurine, in dystrophic muscles [ 8 , 15 17 ].…”
Section: Introductionmentioning
confidence: 99%